Metamorphism and deformation of mafic and felsic rocks in a magma transfer zone, Stewart Island, New Zealand - Vernon, R.; Collins, William; Cook, N. (Wiley - Blackwell, 2012)
In the mingled mafic/felsic Halfmoon Pluton at The Neck, Stewart Island (part of the Median Batholith of New Zealand) some hornblende gabbros and diorites retain magmatic structures, whereas others show evidence of major changes in grain and inclusion shapes, and still others are amphibolite-facies granofelses with few or no igneous relicts. These mafic to intermediate magmas crystallized in felsic magma relatively quickly, with the result that most deformation occurred at subsolidus conditions. It is suggested that mafic-intermediate rocks with predominantly igneous microstructures spent less time in the magmatic system. The metamorphism of the mafic rocks appears to be 'autometamorphic', in the sense that elevated temperatures were maintained by magmatic heat during subsolidus cooling. Elevated temperatures were maintained because of repeated sheet injection and subconcordant dyke injection of hot basaltic and composite mafic-felsic magmas, into a dominantly transtensional, km-scale, outboard-migrating, magmatic shear zone that operated semi-continuously for between c. 140 and c. 130Ma. Complete cooling occurred only when the system evolved to transpressional and the locus of magmatism migrated inboard (southward) between c. 130 and c. 120Ma, associated with solid-state mylonitic deformation. Intermingled granitic rocks escaped metamorphism, because they remained magmatic to lower temperatures, and experienced shorter and lower-temperature subsolidus cooling intervals. However, the felsic rocks underwent relatively high-temperature solid-state deformation, as indicated by myrmekite replacing K-feldspar and chess-board subgrain patterns in quartz; locally they developed felsic mylonites. The felsic rocks were deformed in the solid state because of their high proportion of relatively weak minerals (quartz and biotite), whereas the mafic rocks mostly escaped subsolidus deformation, except in local high-strain zones of hornblende-plagioclase schist, because of their high proportion of relatively strong minerals (hornblende and plagioclase). We suggest that such contrasting microstructural features are diagnostic of long-lived syntectonic magma transfer zones, and contrast with the more typical complex, batholith-scale magma chambers of magmatic arcs.